2018
DOI: 10.1155/2018/8982756
|View full text |Cite
|
Sign up to set email alerts
|

Lepidium meyenii Walp Exhibits Anti-Inflammatory Activity against ConA-Induced Acute Hepatitis

Abstract: Strong inflammation is a prominent pathogenesis of acute hepatitis, which can induce hepatocyte death and lead to liver failure. Lepidium meyenii Walp (Maca) is a traditional herbal medicine mostly used in improving sperm motility and serum hormone levels, etc. However, there are no reports that showed Maca was designed for treating hepatitis so far. Therefore, the protective effects and pharmacological mechanisms of Maca are unknown in hepatitis. In this study, we found that the protective effects of Maca ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…In both models tested here, and as reported before 33,51 , we showed that LPS/ConA resulted in the elevation of the proinflammatory cytokines IL-6, TNF-α and IL-1β, and that IL-2 was specifically induced with ConA treatment. IL-6 is a pleiotropic cytokine which has multiple effects on immune and non-immune cells, including the nervous system 52 .…”
Section: Discussionsupporting
confidence: 91%
“…In both models tested here, and as reported before 33,51 , we showed that LPS/ConA resulted in the elevation of the proinflammatory cytokines IL-6, TNF-α and IL-1β, and that IL-2 was specifically induced with ConA treatment. IL-6 is a pleiotropic cytokine which has multiple effects on immune and non-immune cells, including the nervous system 52 .…”
Section: Discussionsupporting
confidence: 91%
“…Natural killer T (NKT) cells account for about 20–35% of the total lymphocytes in the liver of mice and about 10–15% of total lymphocytes in the human liver;8 studies focused on NKT cells indicate that they play a pro-inflammatory and pro-apoptosis role in liver diseases 810. The NKT cells are one of the most important type of effector cells related to immune liver injury,11 and the imbalance between Tregs and NKT cells distinctly trigger the development of autoimmune responses 12. These studies suggested that once Tregs lose the capacity of inhibiting the proliferation and function of effector T cells, the disease will occur and progress rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, enhancing or sustaining MDSCs suppressive function would be beneficial in inhibiting inflammation and immune disorders [26]. Accumulating evidence indicates that MDSCs can protect against liver injury in AIH patients and experimental immune-mediated hepatitis (IMH) [27][28][29]. Therefore, the regulation of MDSCs is a promising direction to ameliorate immune hepatitis.…”
Section: Ivyspringmentioning
confidence: 99%